PENGARUH MODEL TALKING STICK TERHADAP HASIL BELAJAR IPS SISWA KELAS III SEKOLAH DASAR - Yudit, Harviana; Marli, Suhardi; Halidjah, Siti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the effect of cooperative learning model type talking stick on the results of social science learning class III students of 34 Public Elementary Schools in Pontianak City. The form of research used was quasi experimental design with Nonequivalent Control Group Design. The sample in this study was class III A (control class) and class III C (experimental class) consisting of 60 people. Data collection techniques used are measurement techniques with data collection tools used in the form of a test of student learning outcomes in the form of multiple choices totaling 50 questions. Based on the results of data analysis, the average learning outcomes of control class students were 70.20 while the average learning outcomes of experimental class students was 75.30. The results of testing hypotheses (t-test) using t-test obtained by t count of 3.003 and t table (? = 5% and dk = 58) of 2.00172, indicating that t count (3.003)> t table (2.00172). then Ha is accepted. This means that there is an effect of learning outcomes between students who are taught with cooperative learning models Type talking stick with students taught without cooperative learning model talking stick type. From the effect size (ES) calculation, it is obtained 0.55 (medium criteria). Keywords: influnce, Model Talking Stick, Learning Outcomes